1992
DOI: 10.1097/00006842-199207000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral analysis of heart rate variability in Type As and Type Bs during mental workload.

Abstract: Recently several studies have suggested that there are differences in autonomic balance between Type As and Type Bs. This study evaluates a sympathovagal interaction in Type A (n = 8) and Type B (n = 11) male students during a mental arithmetic task by power spectral analysis of heart rate variability. The low-frequency component to high-frequency component ratio was significantly greater in Type As than in Type Bs during a resting period. No significant differences were found in heart rate changes and blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Evidence that anger can induce myo cardial ischemia by coronary vasoconstriction comes from a study which showed that anger ing an animal by food deprivation can consis tently produce myocardial ischemia and coro nary vasoconstriction in the immediate pos tanger period [147]. Another finding of im portance is that reduced vagal tone or high sympathetic activity, as measured by power spectral analysis of heart rate variability, has been shown in various studies to correlate with angiographic severity [148], risk of ven tricular fibrillation [149], type A behavior [150], and possibly depression [151].…”
Section: Psychiatric Risk Factors For Coronary Artery Diseasementioning
confidence: 99%
“…Evidence that anger can induce myo cardial ischemia by coronary vasoconstriction comes from a study which showed that anger ing an animal by food deprivation can consis tently produce myocardial ischemia and coro nary vasoconstriction in the immediate pos tanger period [147]. Another finding of im portance is that reduced vagal tone or high sympathetic activity, as measured by power spectral analysis of heart rate variability, has been shown in various studies to correlate with angiographic severity [148], risk of ven tricular fibrillation [149], type A behavior [150], and possibly depression [151].…”
Section: Psychiatric Risk Factors For Coronary Artery Diseasementioning
confidence: 99%
“…However, a number of studies suggest that low frequency power (LFP) is a fair estimator of cardiac sympathetic influences (Friedman, Thayer, & Tyrell, 1996;Kamada et al, 1992;Bronis, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Goldberger (1991) suggested that competing influences of both the sympathetic and the parasympathetic branches of the nervous system on the sinus node may be recorded as a type of chaotic heart-rate variability. In humans, this variability has often been determined by differentiating high-and low-frequency components of heart-rate fluctuations (Kamada et al 1992: Kunitake and Ishiko 1992; Murata et al 1992). Goldberger (1991) also suggested that the heart-rate variability may indicate the individual's state of health.…”
mentioning
confidence: 99%